Sleep Quality and Learning in Medical Students: Narrative Review - Gutiérrez Sierra, Manuel (2023)
There has been a great advancement in our understanding of the processes of memory consolidation and the role of sleep in them. There is clear evidence showing that medical students sleep fewer hours and are less satisfied with their sleep quality than other university students. There is also evidence that links sleep and academic performance, however, methodologic differences between studies make it difficult to draw clear conclusions.